Health practices in relation to communicable disease prevention and control in Bangui, Ilocos Norte, and their implications to health education - Malapit, Imelda Delgado 1931- ([Quezon City s.n.], 1972)
Health practices of the people of Bangui, Ilocos Norte were studied, relative to communicable disease prevention and control and the implications of the practices to health education.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Hygiene, Public--Bangui, Ilocos Norte; Health education -- Philippines